Optimalisasi Perlindungan Anak Melalui Sumber Hukum Hindu - Ayu Suseni, Komang (Program Studi Ilmu Hukum Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2021)
Children are the next generation of the nation and every parent's dream. To be able to form children that can be relied upon and become a hope for both parents and useful for the nation and state, the role of parents in guiding and caring for their children is very important. In the Hindu religion books have been explained about children such as Manawa Dharmasastra, Sarasamuccaya, Slokantara and Silakrama. For example in the weda explained Until the age of five, parents must treat their children as kings. In the next ten years as a servant, and after age sixteen and above must be treated as a friend. In this sloka explained, it is better for us to give punishment to children when they make a mistake, as long as it's only natural. If you always spoil a child and have never been banned in any case, then he will get used to what is wrong. According to the Law of the Republic of Indonesia Number 23 Year 2005 concerning Child Protection also confirms that what is meant by a child is someone who is not yet 18 (eighteen) years old, including children who are still in the womb. A child must get good treatment and protection from the womb until birth and growing up. For this reason, the role of parents in understanding and deepening the teachings in the Vedas is very important. We must understand correctly what is the child's needs.